Anomalous magnetic behavior in Ni80Cr20 nanoparticles prepared by physical and chemical methods. (September 2021) - Vishvakarma, Sonu; Srinivas, V.; Ranjan, Prem; Sarathi, R.
Graphical abstract: Highlights: We demonstrate the formation of homogeneous Ni80 Cr20 alloy nanoparticles (NPs) by novel wire explosion process (WEP). Chemical/physical synthesis techniques do not yield desired composition due to incompatible standard reduction potential. The superparamagnetic behavior is identified in 34 nm diameter particles and attributed to uncompensated surface spins. From present study we conclude that WEP is a potential synthesis method to produce alloy NPs with homogeneous composition. Abstract: We report a detailed study of the structural and magnetic properties of Ni80 Cr20 fine particles prepared by physical methods, such as mechanical alloying, wire explosion process (WEP), and chemical methods like sodium borohydride reduction, polyol method. From the analysis of structural and microstructural data, phase formation with the desired composition is confirmed in the particles prepared by the WEP. A comparative study of magnetization data of bulk and nanoparticles of Ni80 Cr20 suggests that a weak magnetic moment develops in nanoparticles due to finite-size effects. Analysis of magnetization data suggests a superparamagnetic (SPM) behavior in the smallest sized (34 nm) particles prepared by WEP, while nanoparticles prepared by other methods show ferromagnetic ground state. Further, it is shown that the origin of weak magnetic moment and development of SPM state in the nanoparticles is due to uncompensated surface spins with a negligible interaction effect.